Research of relative efficiency of switches of the third layer - Кудзиновская, И. П. (Problems of Informatization and Control, 2008)
Advantages of the use of method of thread commutation in networks are analyzed. A mathematical model is built and relative efficiency of application of switches of the third layer is probed as compared to routers depending on descriptions of traffic